2019
DOI: 10.20546/ijcmas.2019.805.283
|View full text |Cite
|
Sign up to set email alerts
|

Varietal Identification Based on Chemical Methods in Different Varieties of Indian Mustard (Brassica juncea (L.) Czern. & Coss.)

Abstract: to distinguish twenty Indian mustard varieties/genotypes based on chemical tests (phenol, modified phenol, KOH, NaOH, Peroxidase and 2, 4-D Auxin). Phenol test grouped variety into three distinct groups viz., dark reddish brown (12 varieties), dark grey (6 varieties) and Dark red (2 varieties). With the help of modified phenol test these varieties were further sub grouped. KOH test grouped varieties into three distinct groups i.e., dark brown (6 varieties), brown (5 varieties) and light brown (9 varieties). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Based on the response of 200 germplasm lines of rice to chemical tests, a comprehensive key has been developed for rapid identification of rice germplasm accessions. In conclusion, it was observed that the statement, "individually chemical tests are of limited value, but when used in conjunction with each other can separate almost any number of rice varieties[24][25][26][27] was proven in the present study where no single chemical test could distinguish even a single variety but when these tests were used in combination could identify all the two hundred varieties individually. Hence these simple, rapid and reliable tests are of immense value for the varietal identification purpose in rice crop.…”
mentioning
confidence: 56%
“…Based on the response of 200 germplasm lines of rice to chemical tests, a comprehensive key has been developed for rapid identification of rice germplasm accessions. In conclusion, it was observed that the statement, "individually chemical tests are of limited value, but when used in conjunction with each other can separate almost any number of rice varieties[24][25][26][27] was proven in the present study where no single chemical test could distinguish even a single variety but when these tests were used in combination could identify all the two hundred varieties individually. Hence these simple, rapid and reliable tests are of immense value for the varietal identification purpose in rice crop.…”
mentioning
confidence: 56%
“…Identification of plant variety or cultivar is one of the essential factors in agricultural system [21,22]. Varietal identification is crucial to ensure the identity of particular genotypes or plant varieties.…”
Section: Resultsmentioning
confidence: 99%